A Multicenter, Prospective Study of a New Fully Covered Expandable Metal Biliary Stent for the Palliative Treatment of Malignant Bile Duct Obstruction - Bret T. Petersen; Michel Kahaleh; Richard A. Kozarek; David Loren; Kapil Gupta; Thomas Kowalski; Martin Freeman; Yang K. Chen; Malcolm S. Branch; Steven Edmundowicz; Michael Gluck; Kenneth Binmoeller; et al. (Gastroenterology Research and Practice)
Background and Study Aims. Endoscopic placement of self-expanding metal stents (SEMSs) is indicated for palliation of inoperable malignant biliary obstruction. A fully covered biliary SEMS (WallFlex Biliary RX Boston Scientific, Natick, USA) was assessed for palliation of extrahepatic malignant biliary obstruction. Patients and Methods. 58 patients were included in this prospective, multicenter series conducted under an FDA-approved IDE. Main outcome measurements included (1) absence of stent occlusion within six months or until death, whichever occurred first and (2) technical success, need for reintervention, bilirubin levels, stent patency, time to stent occlusion, and adverse events. Results. Technical success was achieved in 98% (57/58), with demonstrated acute removability in two patients. Adequate clinical palliation until completion of followup was achievedin 98% (54/55) of evaluable patients, with 1 reintervention due to stent obstruction after 142 days. Mean total bilirubin decreased from 8.9 mg/dL to 1.2 mg/dL at 1 month. Device-related adverse events were limited and included 2 cases of cholecystitis. One stent migrated following radiation therapy. Conclusions. The WallFlex Biliary fully covered stent yielded technically successful placement with uncomplicated acute removal where required, appropriate reduction in bilirubin levels, and low rates of stent migration and occlusion. This SEMS allows successful palliation of malignant extrahepatic biliary obstruction.